5(x+3)+8=-2(x-8)

Simple and best practice solution for 5(x+3)+8=-2(x-8) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5(x+3)+8=-2(x-8) equation:


Simplifying
5(x + 3) + 8 = -2(x + -8)

Reorder the terms:
5(3 + x) + 8 = -2(x + -8)
(3 * 5 + x * 5) + 8 = -2(x + -8)
(15 + 5x) + 8 = -2(x + -8)

Reorder the terms:
15 + 8 + 5x = -2(x + -8)

Combine like terms: 15 + 8 = 23
23 + 5x = -2(x + -8)

Reorder the terms:
23 + 5x = -2(-8 + x)
23 + 5x = (-8 * -2 + x * -2)
23 + 5x = (16 + -2x)

Solving
23 + 5x = 16 + -2x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '2x' to each side of the equation.
23 + 5x + 2x = 16 + -2x + 2x

Combine like terms: 5x + 2x = 7x
23 + 7x = 16 + -2x + 2x

Combine like terms: -2x + 2x = 0
23 + 7x = 16 + 0
23 + 7x = 16

Add '-23' to each side of the equation.
23 + -23 + 7x = 16 + -23

Combine like terms: 23 + -23 = 0
0 + 7x = 16 + -23
7x = 16 + -23

Combine like terms: 16 + -23 = -7
7x = -7

Divide each side by '7'.
x = -1

Simplifying
x = -1

See similar equations:

| 3r+-16r+9r=4 | | 8x-4=5x+10+4x+28 | | 3r+16r+9r=4 | | -4j+10=-8j-10 | | 6+2x-5=8x+37-2x | | 19r-18r+3r-3r=15 | | 9x=-13x+9 | | -6y+6=-3y | | 42.3=3x | | 16h-12h=12 | | 2b-b=17 | | 2b-4(b-4)=b+3 | | 5(x-2)=2(x+5)+10 | | 4x^2-19x+5=0 | | 4-5x=-3x | | -2w+4=4w-8 | | 11(2x-1)=8(2x+1)+11 | | 9x+3=-8x+12-5x | | 3x+2y-2(5x-4y)= | | 8r-5r+2=9r+2-r | | 3(3x+1)=-4(2x-3)-5x | | -66-7x=-13x+18 | | (5x+3x)+(7x+3)= | | (a-5)(5a-1)= | | 2.798x+4=17.9 | | 10(-2x+1)=-19(r+1) | | -3x-16=2x+4 | | sqrtx+10=2 | | (4+1.3)*2.1= | | 15(4y+14)= | | 5x-(-2)=3 | | -2x+9x-4x=0 |

Equations solver categories